Unveiling Global Healthcare Economics and Worker Migration Post-COVID-19: A Bibliometric Approach - Carrenina Bonita Manek Here; Aluisius Hery Pratono (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
This article examines the evolving dynamics of global healthcare migration by identifying key topics, gaps, and economic frameworks that shape current debates on labour mobility. A bibliometric analysis of 933 manuscripts from Google Scholar, including 471 indexed in Scopus and Web of Science, published between 2020 and 2024, captures both the COVID-19 and post-pandemic periods. Using VOSviewer, five thematic clusters emerge across 79 keywords: (1) labour market inefficiencies in the Gulf Cooperation Council, (2) healthcare technology and dynamic labour markets, (3) efficiency and equity in migrant healthcare labour markets, (4) costs of employing expatriate healthcare workers, and (5) economics of digital transformation in healthcare work. The study highlights how labor market structures, economic incentives, and transaction costs shape the mobility of healthcare workers. Broader frameworks (i.e., systems theory, migration and labour market theories, human capital theory, technology acceptance, and digital economy perspectives) inform the analysis. As a novel contribution, this study provides a post-pandemic data-driven mapping of healthcare labour migration that integrates bibliometric analysis with economic theory to uncover underexplored digital and systemic drivers of global healthcare mobility. The findings call for policies that reduce wage inequities, lower the costs of migrant employment, strengthen the integration of human capital, and foster a resilient, future-ready healthcare workforce.